PEMBERDAYAAN KELOMPOK TANI BUDI MAKMUR IX MELALUI PEMANFAATAN VERMIKOMPOS SEBAGAI PUPUK TANAMAN DAN PAKAN IKAN LELE (Clarias SP.) - Hasna Dama; Shindy Hamidah Manteu; Arafik Lamadi (Jurnal Abdi Insani, 2026)
Vermicompost is an organic fertilizer produced from the decomposition process of organic materials (such as vegetable waste and other organic materials) which is assisted by the decomposting process by earthworms. Vermicompost is used as an environmentally friendly alternative fertilizer, it can improve soil structure, increase fertility and help optimal plant growth. The earthworms harvested from vermicomposting can be used as feed for catfish. The purpose of this community service partnership is to introduce vermicomposting to the Budi Makmur IX farmer group and provide guidance on how to make vermicompost and how to use it for plants and as catfish feed. The approaches used in this PKM program include outreach, training, mentoring, and evaluation. Based on the results of this community service, the farmer group received education about vermicomposting and was able to create alternative fertilizers and supplemental feed for catfish.